Dangerous trade arms exports, human rights, and international reputation - Erickson, Jennifer L. (Columbia University Press, 2015)
The United Nations's groundbreaking Arms Trade Treaty (ATT), which went into effect in 2014, sets legally binding standards to regulate global arms exports and reflects the growing concerns toward the significant role that small and major conventional arms play in perpetuating human rights violations, conflict, and societal instability worldwide.